1996
DOI: 10.1016/0014-5793(96)00959-3
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin and mitochondrial function in glutamate‐induced neuronal cell death

Abstract: We have previously reported that glutamate can trigger a succession of necrosis and apoptosis in cerebellar granule cells (CGC). Since specific blockers of the N-methyl-aaspartate (NMDA) receptor channel prevented both types of cell death, the role of Ca2+-dependent processes in the initiation of glutamate toxicity was further investigated. We examined the possible involvement of mitochondria and the role of the Ca2÷/ calmodulin-regulated protein phosphatase, calcineurin, in the development of either type of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
149
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(156 citation statements)
references
References 37 publications
(40 reference statements)
7
149
0
Order By: Relevance
“…Dephosphorylated Bad translocates from the cytosol to the mitochondria where it inhibits antiapoptotic activity of Bcl-2 and Bcl-x L , ultimately, leading to cell death (Desagher and Martinou, 2000, for review). In accordance, was found to decrease apoptosis of cerebellar granule and cortical cultures after exposure to glutamate (Ankarcrona et al, 1996;Asai et al, 1999) or to amyloidogenic peptides (Agostinho and Oliveira, 2003). FK506 also prevented calcineurin-mediated dephosphorylation of nitric oxide synthase, leading to neuroprotection (Dawson et al, 1993;Nishino et al, 1996).…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Dephosphorylated Bad translocates from the cytosol to the mitochondria where it inhibits antiapoptotic activity of Bcl-2 and Bcl-x L , ultimately, leading to cell death (Desagher and Martinou, 2000, for review). In accordance, was found to decrease apoptosis of cerebellar granule and cortical cultures after exposure to glutamate (Ankarcrona et al, 1996;Asai et al, 1999) or to amyloidogenic peptides (Agostinho and Oliveira, 2003). FK506 also prevented calcineurin-mediated dephosphorylation of nitric oxide synthase, leading to neuroprotection (Dawson et al, 1993;Nishino et al, 1996).…”
Section: Introductionmentioning
confidence: 59%
“…This calcium-dependent phosphatase has been described to be involved in many pathways that ultimately lead to cell death (Asai et al, 1999;Springer et al, 2000). Accordingly, inhibition of calcineurin as a relevant event in FK506-mediated protective effects has been demonstrated by many authors (Ankarcrona et al, 1996;Asai et al, 1999;Mobley and Agrawal, 2003;Nishino et al, 1996;Stevens et al, 2003). However, numerous other studies have excluded a substantial contribution of inhibited calcineurin for neuroprotection exerted by FK506 (Sabatini et al, 1997;Snyder et al, 1998;Toung et al, 1999;Yardin et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example of cells treated with 300 nM Pc 4 and 90 mJ/cm 2 of red light is displayed in Figure 4. In control untreated cells, JC-1 fluorescence was found to have a perinuclear distribution and a punctuate pattern, indicating its location in mitochondria (Ankarcrona et al, 1996). A slight reduction in JC-1 fluorescence was observed in cells 15 min after receiving 90 mJ/cm 2 .…”
Section: Resultsmentioning
confidence: 86%
“…Evidence is also available that the excitotoxic injury can produce hybrid forms of cell death, existing on a continuum between the classically defined apoptosis and necrosis [38,39,43], and is likely to depend on the degree of insult and the sensitivity of the exposed neurones. Time-dependent studies of glutamate exposure to cultured neuronal populations showed that the excitotoxins induce early necrosis and delayed apoptosis [36,44]. There is also evidence that the necrotic neurons may completely recover to undergo apoptotic transformation later [44].…”
Section: Discussionmentioning
confidence: 99%